A novel harm reduction approach for oncology outpatients who smoke and refuse traditional tobacco treatment: a protocol for a type 1 hybrid effectiveness-implementation trial - Tracy T. Smith; Paris Bedford; Matthew J. Carpenter; Naomi Brownstein; Shikhar Mehrotra; Benjamin A. Toll; Alana M. Rojewski (Addiction Science & Clinical Practice, 2026)
Abstract Background Smoking rates are high among patients in cancer care, and improving quit rates among these patients is critical for improving survival outcomes. Yet, many oncology outpatients do not receive tobacco treatment, and a sizeable portion even refuse available evidence-based resources. E-cigarettes deliver lower levels of known carcinogens compared to cigarettes, and several rigorous trials have shown higher quit rates among people who receive e-cigarettes compared to those who receive nicotine replacement therapy. Switching from cigarettes to e-cigarettes reduces exposure to carcinogens and may be an appealing harm reduction intervention for patients in cancer care who refuse traditional treatment. The present protocol describes an ongoing type 1 hybrid effectiveness-implementation trial among oncology outpatients at an NCI-designated cancer center to compare rates of switching to e-cigarettes to standard care, and advance understanding of key barriers and facilitators of implementation processes. Methods Adults who smoke cigarettes and refuse all components of traditional tobacco treatment through an opt-out tobacco treatment service are randomized to receive either (1) a 13-week supply of e-cigarettes and a workbook for switching to e-cigarettes or (2) a workbook for quitting smoking. Participants assigned to e-cigarettes are instructed to set a switch date within two weeks of randomization, to use their e-cigarette ad libitum in advance of their switch date, and to stop smoking cigarettes and exclusively use their e-cigarette on their switch date. Participants complete biweekly assessments through the end of product provision and additional follow ups through 6 months. The primary outcome is complete switching (7-day point prevalence abstinence confirmed by expired breath carbon monoxide ≤ 5ppm) at 6 Months. Secondary outcomes include implementation processes, biomarkers of cancer risk, and health-related quality of life. Discussion This study examines a novel approach to harm reduction among oncology outpatients who refuse traditional tobacco treatment. Integrating effectiveness and implementation results helps to engage this population in harm reduction and provides critical evidence to refine delivery and planning for implementation. The proposed trial is highly significant, regardless of the results, and has the potential to influence harm-reduction approaches to tobacco use among patients in cancer care. Trial registration The current study was registered on clinicaltrials.gov on June 26, 2025 (NCT07039292).